Featured Cover - Leberecht, Kerstin M.; Ritter, Simon M.; Lapp, Christian J.; Klose, Lukas; Eschenröder, Julian; Scholz, Christian; Kühnel, Sebastian; Stinnesbeck, Wolfgang; Kletzin, Arnulf; Isenbeck‐Schröter, Margot; Gescher, Johannes (Geobiology, 2022)
Cover Caption: The cover image is based on the Research Article Microbially promoted calcite precipitation in the pelagic redoxcline: Elucidating the formation of the turbid layer by Kerstin M. Leberecht, et al., https://doi.org/10.1111/gbi.12492